Life and Death in Soweto - Sim, Duncan (Little Bird ; BBC, 2002)
Soros Documentary Fund The film looks at Soweto, South Africa, over a period of four years through the eyes of its inhabitants. The stories of these individuals are told against the backdrop of a society destroyed under apartheid, and slowly rebuilding.